Improving self-confidence and speaking skills in elementary students through action-based learning - Ardhian Zahroni; Mohammad Syaifuddin; Khozin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Low self-confidence and limited oral proficiency remain significant hurdles for young language learners, often exacerbated by high affective filters and conventional, non-interactive teaching methods. This study aims to evaluate the effectiveness of Action-Based Learning (ABL), integrated with gamified digital tools, in enhancing English-speaking skills and self-confidence among elementary school students. Drawing on constructivist learning theory and the Affective Filter Hypothesis, the pedagogical framework was operationalized through iterative "act-and-reflect" cycles, supported by digital platforms such as Wordwall, to foster a low-anxiety, high-engagement classroom environment. The research employed a quasi-experimental pretest-posttest control group design involving 50 fifth-grade students (n=25 per group). Data were gathered through standardized speaking tests, Likert-scale questionnaires, and classroom observations, and analyzed using paired and independent t-tests. Findings revealed that the experimental group achieved substantial gains in self-confidence (Mdif = 1.30, p < .001) and English-speaking skills (Mdif = 1.25, p < .001). Post-test comparisons confirmed that the ABL group significantly outperformed the control group in both confidence (t = 4.51, p < .001) and oral performance (t = 3.35, p = .0012). These results provide empirical evidence that experiential "learning-by-doing" tasks and gamification effectively mitigate Foreign Language Speaking Anxiety (FLSA) while bolstering communicative competence and self-efficacy. Consequently, ABL is recommended as a strategic pedagogical tool to evolve traditional instructional methods and foster early language success in elementary contexts.